2016
DOI: 10.1016/j.jadohealth.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful Use of a Confidential Adolescent Patient Portal

Abstract: Institutional decisions for implementing meaningful use requirements can align with goals of adolescent health. Patient portals can enhance adolescent health care quality and adolescents readily use a confidential portal. Implementation of meaningful use requirements should be checked against adolescent health care needs to maximize confidentiality and promote health communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 8 publications
1
56
1
Order By: Relevance
“…Although adolescent patients are eligible for their own MHAV accounts at VUMC, over 83% of the logins for these patients were by done by surrogate users. In contrast, another study of a patient portal specifically designed for adolescent health care needs in the primary care setting saw frequent access by adolescent users [30]. In our study, the number of "self " logins for teenage users increased with the patient age, which could be attributed to adolescent patients becoming more involved in their care as they mature, being promoted by providers as recommended by the AAP, or becoming simply more familiar with using MHAV.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…Although adolescent patients are eligible for their own MHAV accounts at VUMC, over 83% of the logins for these patients were by done by surrogate users. In contrast, another study of a patient portal specifically designed for adolescent health care needs in the primary care setting saw frequent access by adolescent users [30]. In our study, the number of "self " logins for teenage users increased with the patient age, which could be attributed to adolescent patients becoming more involved in their care as they mature, being promoted by providers as recommended by the AAP, or becoming simply more familiar with using MHAV.…”
Section: Discussioncontrasting
confidence: 73%
“…Differences in adolescent usage can be attributed in part to the institutional privacy and confidentiality policies. At VUMC, our approach favors parental access to a children's information whereas portals that prioritize adolescent confidentiality, allowing parents only limited information, show higher rates of adolescent usage [30]. One organization that required adolescent assent for proxy access showed low rates of registration for such accounts, suggesting that adolescents may have reservations about sharing their health data with their parents [32].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although Irizarry et al reported pediatric caregivers have the most interest in portals, there are few studies or systematic reviews examining pediatric portals. 9,22,[25][26][27] Objectives This study examined patterns of patient portal codes and activation at two tertiary academic pediatric hospitals, one in Colorado and the other in Southern California, by race/ ethnicity, preferred language, patient gender, and activation by caregiver proxy or adolescent patient. One site had both English and Spanish portal information and activation materials and the other provided English-only access.…”
Section: Portal Utilization Barriersmentioning
confidence: 99%